Atrial Natriuretic Peptide: A Potential Early Therapy for the Prevention of Multiple Organ Dysfunction Syndrome Following Severe Trauma. Issue 2 (February 2018) - Zhang, Rong-Wei; Liu, Li-Li; Zeng, Lan-Lan; Li, Rui-Jie; Shen, Ye-Hua; Zhang, Bin; Liu, Zi-Zhuo; Chen, Meng-Fei; Jiang, Sheng-Mao; Jiang, Li-Bing; Zhao, Xiao-Gang; Jiang, Shou-Yin
Abstract : ABSTRACT: Trauma remains a tremendous medical burden partly because of increased expenditure for the management of multiple organ dysfunction syndrome (MODS) developed during hospital stay. The intestinal barrier injury continues to be a second insult resulting in MODS which currently lacks efficient strategies for prevention. Recent studies have uncovered multi-organ protective benefits of atrial natriuretic peptide (ANP) in cardiovascular disease. However, the role of ANP in the prevention of MODS following severe trauma has not been understood. In our laboratory study, 1-h infusion of exogenous ANP during hemorrhagic shock following severe trauma induced high-level expression of endogenous serum ANP after 24 h, this effect was related to the improved level of functional biomarkers in multiple organs. Such phenomenon has not been found in other laboratories. A thorough literature review consequently was performed to uncover the potential mechanisms, to appraise therapy safety, and to propose uncertainties. In severe trauma, short-term exogenous ANP therapy during hemorrhagic shock may promote sustained endogenous expression of ANP from intestinal epithelium through activating a positive feedback loop mechanism involving phospholipase C-γ1 and reactive oxygen species crosstalk. This feedback loop may prevent MODS through multiple signaling pathways. Administration of ANP during hemorrhagic shock is thought to be safe. Further studies are required to confirm our proposed mechanisms and to investigate the dose, duration, and timing of ANP therapy in severe trauma.